Progress of Biogas Industry in Malaysia: Cattle Manure as Potential Substrate for Biogas Production and Issue and Challenges - Gopinathan M.; Kumaran P.; Rahaman A.A.; Bt Ismail Z. (IEEE Computer Society, 2023)
Biogas; Crude oil; Effluents; Electric power transmission networks; Electric utilities; Energy policy; Fertilizers; Manures; Natural gas; Natural gas deposits; Natural gasoline plants; Petroleum deposits; Planning; Renewable energy resources; Substrates; Sustainable development; Biogas plants; Cattle manures; Codigestion; Feed-in tariff; Renewable energies; Electric power generation